Bank stability, sovereign debt and derivatives - Falzon, Joe, 1958- (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
This selection of papers were presented at the Wolpertinger Conference held in Valletta, Malta, 2012 and provide insights into bank performance, banking risk, securitisation, bank stability, sovereign debt and derivatives.
Includes bibliographical references and index.
oif 12/06/15
Loan
Keywords: Finance and Accounting; Bank management; Debts, Public; Derivative securities